2013
DOI: 10.7860/jcdr/2013/4719.2800
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Drug Use in Acute Fever by General Practitioners (GPs) in Pune City, India

Abstract: Objectives: 1) To determine the WHO Prescribing Core Drug Use (PCDU) indicators in the management of acute fever (of less than 2 weeks duration) of the MBBS (allopathic) and BAMS (ayurvedic) General Practitioners (GPs) in Pune city. 2) To verify the appropriateness of the treatment. and 3) To compare the above parameters of the MBBS and the BAMS practitioners. Methods:Pune city was divided in five zones, north, south, east, west and central. A list of doctors was obtained from the Indian Medical Association an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
(2 reference statements)
1
7
0
Order By: Relevance
“…Among the 21 studies that reported the total number of patients attending a certain facility at the time of data collection [27,28,30,32,36,38,39 [46,57]. We could not identify any specific pattern in the distribution of antibiotic prescription rates across levels of country income, partly due to small sample sizes.…”
Section: Prevalence Of Antibiotic Prescriptionmentioning
confidence: 85%
See 1 more Smart Citation
“…Among the 21 studies that reported the total number of patients attending a certain facility at the time of data collection [27,28,30,32,36,38,39 [46,57]. We could not identify any specific pattern in the distribution of antibiotic prescription rates across levels of country income, partly due to small sample sizes.…”
Section: Prevalence Of Antibiotic Prescriptionmentioning
confidence: 85%
“…In most cases, the authors made their judgment based on national and/or international guidelines for treatment of key conditions. Among the 9 studies that assessed the rationality of antibiotic prescriptions [36,39,46,53,55,62,64,65,67], the proportion judged inappropriate ranged widely, reflecting the significant differences in study designs as well as in the sets of criteria that were adopted to determine the outcome ( Table 2). The lowest level of inappropriate prescription (7.9%; 95% CI: 4.6%-12.5%) was reported in a study conducted in Zambia that included 537 children aged <5 years presenting with an acute respiratory syndrome, of whom 37.6% (95% CI: 33.5%-41.9%) were given antibiotics [39].…”
Section: Inappropriate Antibiotic Prescriptionmentioning
confidence: 99%
“…In such cases, antibiotic prescription is nonetheless still perceived as being essential. A parallel can be drawn with general medicine: for example, the use of antibiotics by doctors in case of a fever [ 12 ] seems comparable to the use of antibiotics by dentists in case of exacerbated pain [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A combination of nimesulide and paracetamol was found to be the most preferred drugs by physician for fever. Patients who were prescribed with NSAIDs also received drugs to prevent gastritis [ 10 ]. Vitamins and supplements were also found to be widely prescribed medication.…”
Section: Resultsmentioning
confidence: 99%